Conduction disorders after transcatheter aortic valve implantation: A comparison between SAPIEN 3 and SAPIEN 3 Ultra balloon-expandable valves - Monizzi, Giovanni; Olivares, Paolo; Makmur, Giulio; Fabbiocchi, Franco; Grancini, Luca; Mastrangelo, Angelo; Ferrari, Cristina; Galli, Stefano; Montorsi, Piero; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2022)
Background Conduction disorders (CD) are the most common complications after Transcatheter Aortic Valve Implantation (TAVI). The last generation of Edwards balloon expandable valves, the SAPIEN 3 Ultra (S3U), is provided with an external sealing skirt that aims to further reduce paravalvular leakage (PVL) compared to SAPIEN 3 (S3) and could potentially lead to higher CD rate. We sought to investigate the rate of new-onset CD in patients undergoing TAVI with the S3 or S3U valve. Methods We included 582 consecutive patients undergoing TAVI in a single high-volume Center. Patients with previously implanted pacemaker and Valve in valve procedures were excluded. CD rate was evaluated early after implantation and at discharge. Results No significant difference in the overall CD rate was found between S3 and S3U patients both immediately after the procedure (S3 45.5% vs. S3U 41.8%, p = 0.575) and at discharge (S3 30.4% vs. S3U 35.6%, p = 0.348) with low rate of permanent pacemaker implantation (S3 6.3% vs. S3U 5.5%, p = 0.749). No significant differences were found also in patients with pre-existing atrial fibrillation (S3 8.2% vs. S3U 5%, p = 0.648). A significantly lower rate of PVL was found with S3U compared to S3 (S3 42% vs. S3U 26%, p = 0.007). According to the manufacturer’s guidelines we confirmed that S3U were implanted in a significantly higher position compared to S3 (S3 4.89 ± 1.57 mm vs. S3U 4.47 ± 1.36 mm, p = 0.001). Conclusion No significant difference in the rate of CD, including the need for PPM implantation, was found in patients undergoing TAVI with the S3 compared to S3U. Moreover, S3U significantly reduced the PVL rate.